Markers of Basement Membrane Remodeling Are Associated With Higher Mortality in Patients With Known Atherosclerosis - Signe Holm Nielsen; Christoffer Tengryd; Andreas Edsfeldt; Susanne Brix; Federica Genovese; Eva Bengtsson; Morten Karsdal; Diana J. Leeming; Jan Nilsson; Isabel Goncalves (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
Background Patients with atherosclerosis have a high risk of cardiovascular events and death. Atherosclerosis is characterized by accumulation of lipids, cells and extracellular matrix proteins in the intima. We hypothesized that dysregulated remodeling of the basement membrane proteins may be associated with clinical outcomes in patients with atherosclerosis. Methods and Results Neoepitope fragments of collagen type IV (C4M) and laminin (LG1M) were assessed by ELISAs in serum from 787 endarterectomy patients. Matrix metalloproteinases were measured using proximity extension assay and correlated to C4M and LG1M levels using Spearman correlations. A total of 473 patients were followed up for 6 years using national registers, medical charts, and telephone interviews. The incidence of cardiovascular events, cardiovascular mortality, and all‐cause mortality were associated to levels of C4M and LG1M using Kaplan–Meier curves and Cox regression analyses. A total of 101 patients had cardiovascular events, 39 died of cardiovascular mortality, and 64 patients died from all‐cause mortality. C4M levels were increased in patients with symptomatic carotid atherosclerotic disease before surgery (P=0.048). High C4M and LG1M levels were associated with increased risk of all‐cause mortality (P=0.020 and 0.031, respectively) and predicted all‐cause death together with glomerular filtration rate and diabetes mellitus. Conclusions High LG1M and C4M levels were associated with all‐cause mortality, together with glomerular filtration rate and diabetes mellitus. These novel biomarkers need further evaluation but might be tools to identify high‐risk patients.